Research methodology and data analysis - Zainudin Awang (Penerbit Universiti Teknologi Mara, 2012)
This book provides direction in doing research especially towards the understanding of research objectives, research questions, and research hypotheses. This book also guides in research methodology such as the methods of designing a questionnaire, methods of sampling, methods of data collection, and methods of data analysis.